Pembelajaran Tahfizh Al Qur’an Pesantren Nurul Huda Mergosono Malang - Iqlima Zahari (Ta'allum: Jurnal Pendidikan Islam, 2017)
Learning is a process, way, and action of human for learning. Learning combines about human, facilities, devices, and procedure mutual to influence human purpose to learn. Memorize the Holy Quran is someone who memorize the Holy Quran or understand The Holy Quran by heart. This research is carried in Nurul Huda Boarding School Mergosono Malang. In this Boarding School the students are educated to understand the classical Islamic scripture. This research is focused  on memorizing  Holy Quran program because memorize Holy Quran program in Nurul Huda Boarding School has a target in which the student can finalize their memorize in 3 years. This research case study is to know how about learning memorizes of the Holy Quran in Nurul Huda Boarding School Mergosono Malang. Moreover, it is to know the difficulties and obstacles memorizing the Holy Quran and to know whether the students can finish their memorization in 3 years or not. This research is a Qualitative research method. The data resources are primer and seconder data. The accumulation data combines with observation, interview, documentation, and inquiry. The analysis data to pass with rank data, course data, verifying and comparative analysis.